Evolution of sediment provenances and transport processes in the central Bay of Bengal since the Last Glacial Maximum. (20th August 2022) - Ye, Wenxing; Liu, Shengfa; Fan, Dejiang; Zhang, Hui; Cao, Peng; Pan, Hui-Juan; Li, Jingrui; Li, Xiaoyan; Fang, Xisheng; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Shi, Xuefa
Abstract: To investigate the evolution of sediment provenances and transport processes in the central Bay of Bengal (BoB) since the Last Glacial Maximum, we present a comprehensive study on the grain size, clay minerals, rare earth elements, and accelerator mass spectrometry (AMS) 14 C analyses of the core BoB-24 sediments. Six AMS 14 C dates were obtained from planktonic foraminiferal Neogloboquedrina dutertrei ( N . dutertrei ) extracted from the core to reconstruct a reliable age model. The assemblage of clay minerals and the (La/Yb)UCC –δEu relationship indicated that the core contained a mixture of sediments from the Himalayas and Indian Peninsula. These results showed that the Himalayas were the main source of erosional materials during 25–6.5 ka BP, whereas those from the Indian Peninsula increased since the mid-Holocene. Between 25 ka BP and 12 ka BP, the sea level was relatively low, and a large amount of terrigenous detrital material were directly transported from the Himalayas and the Tibet Plateau to the study area by submarine canyons, forming a deposition center on the Bengal Fan. Between 12 ka BP and 6.5 ka BP, the sea level gradually rose and the Indian summer monsoon gradually strengthened, whereas the sedimentation rate and the amount of material transported from the Ganges–Brahmaputra River decreased greatly; the deposition center transferred from the Bengal Fan to the shelf of the BoB. Since 6.5 ka BP, the sea level has risen, reaching its present position. A high sea level and a strengthened East Indian Coastal Current resulted in an increase of material contribution from India, while the deposition center was on the shelf of the BoB. Overall, this study confirmed that both sea level fluctuations and variations of the Indian summer monsoon controlled the evolution of sediment provenances in the central BoB and transfer of the deposition center from the Bengal Fan to the continental shelf. This typical sedimentary pattern observed in the northeastern Indian Ocean improves our general understanding of past land–sea interactions. Graphical abstract: Image 1